That forms a right triangle, so use the Pythagorean theorem. 5^2+2^2=c^2
25+4=c^2
c=√29
Hope this helps
Answer:
A. f(x) = x^2 + 4x + 3
D. f(x) = -2x^2 - 8x + 1
Step-by-step explanation:
The axis of symmetry is found by h = -b/2a where ax^2 +bx +c
A. f(x) = x^2 + 4x + 3
h = -4/2*1 = -2 x=-2
B. f(x) = x^2 - 4x - 5
h = - -4/2*1 = 4/2 =2 x=2 not -2
C. f(x) = x^2 + 6x + 2
h = -6/2*1 = -3/2 = x=-3/2 not -2
D. f(x) = -2x^2 - 8x + 1
h = - -8/2*-2 = 8/-4 =-2 x=-2
E. f(x) = -2x^2 + 8x - 2
h = - 8/2*-2 = -8/-4 =2 x=2 not -2
Answer:
D
Step-by-step explanation:
Lets go case by case.
Given the roots, a factor will be part of the equation if for some of the roots the factor becomes null, i.e., equal to 0.
Is there any root that makes (x+3)=0? No, as it only becomes 0 for x = - 3 and -3 is not a root. So A NO!
Is there a root that makes (x-1)=0? No, as it only becomes 0 for x=1 and 1 is not a root. So B NO!
(x-4)=0 only for x=4, and as 4 is not a root, C NO!
The last, (x-3)=0 if x=3. As 3 is one of the roots, (x-3) is a factor of our equation!
D is the only correct option!
Answer:
1/25
Step-by-step explanation:
We can see that in this pattern, the denominator and the numerator of the next fraction cancel out; they're the same.
(1/2) x (2/3) x (3/4) = 1/4 (do you see it?)
The only things that do not cancel out are the numerator of the first fraction and the denominator of the last. So, in the end, the answer will be 1/25.
Hope this helps!
f(x) = 2x - 7 This should be the answer!!